Finland : Selected Issues. (IMF Staff Country Reports; Country Report ;, 2014)
This Selected Issues paper on Finland discusses that the country is struggling to recover from the Great Recession, indicating that deeper, structural issues may be holding back growth. Estimates of potential output for Finland are an important part of the toolkit for policymakers-but they come with a degree of uncertainty. As this paper illustrates, the use of different methodologies and assumptions can lead to different results. However, there are indications that Finnish potential output growth is low at this juncture. From 1997 to 2007, potential growth, independent of the choice of smoothing, averages 3.2 percent per year. In 2013, that average has dropped to 0.2 with several of the models producing negative growth. This result indicates that the lack of a recovery in Finland is largely structural in nature. Therefore, any indication that the output gap is closing is due to falling potential rather than a pickup in growth. This leads to the advantages of structural reforms aiming to enhance Finland's long-term capacity. Total factor productivity enhancing measures could be crucial in helping the economy recover despite the time it takes to implement them.